Oral surgical treatment of patients suffering from haemophilia - Tijanić Miloš R.; Stojanović Simona M.; Burić Kristina N.; Stojković Branislava B. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2024)
Introduction: Haemophilia is one of the most common haemorrhagic diseases from the group of coagulopathies and results from a deficiency of factors responsible for the first phase of coagulation. Aim: This informative paperwork aims to highlight the principles of oral surgical treatment of patients with haemophilia. Material and methods: The available literature was analysed to indicate the basic characteristics of haemophilia (clinical manifestation, possibilities of treatment and prophylaxis of the disease) with special reference to specificity and principles of dental oral surgical treatment of patients with haemophilia. Conclusion: The treatment of patients with haemophilia is considered one of the riskiest in everyday dental practice. Despite this, dental interventions can be successfully and safely performed. However, the dentist must be acquainted with the nature of the disease, its symptoms and the severity of the clinical picture. Furthermore, the dentist needs to know what kind of therapy the patient receives for the treatment of haemophilia, whether the patient has been diagnosed with inhibitors to the coagulation factor, and whether the patient has concomitant diseases with special reference to possible infectious diseases. Along with that, the key to a successful and safe intervention lies in a well-planned preoperative, perioperative and postoperative treatment of patients with haemophilia.